Handling the cornucopia. (Economist, 2010)
The article examines information resources and knowledge management. The tremendous increase in the amount of information available to human beings requires prior processing by computers and systems such as machine learning and visualization to become usable and comprehensible. Problems with computer systems, database management software and other technologies involved in this process are considered.